Morpho - agronomic diversity in Eleusine coracana (L.) Gaertn landraces from Maharashtra State (India) - G. Auti, S.; Kazi, Tahsin; Ahire, D.D. (Journal of Scientific Agriculture, 2017)
Sixty four finger millet [Eleusine coracana (L.) Gaertn] landraces and 2 cultivars were evaluated for yield contributing and morpho-agronomic characters. All the landraces were collected from Western Ghats zone of Maharashtra. Collected landraces were cultivated at Nashik (Maharashtra) and 5 representatives of each were evaluated for head weight, height, 1000 seed weight, tillers, panicle length, extra finger, number of grains/spikelet, number of fingers/ head, days to 50% flowering and days to maturity. Obtained data was used to determine GCV, PCV and correlation studies. A good amount of variability was found for all the selected characters. Among the characters highest GCV and PCV was recorded for tillers (54.95% and 71.38%). All the characters showed higher PCV values which indicate the influence of the environment. All the characters except height and tillers exhibited higher level of correlation. Heritability estimates ranged from 90.03 % for 1000 seed weight to lowest 44.03 % for height. 1000 seed weight exhibited high heritability coupled with low genetic advance. Obtained results revealed the existence of variability for the character studied. Present studies will be useful for selection of potential characters which could be used in the genetic improvement or selection program of Finger millets.